2021
DOI: 10.1159/000516637
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Renal Oxygenation and Hemodynamics in Patients with Chronic Kidney Disease by Blood Oxygenation Level-dependent Magnetic Resonance Imaging and Intrarenal Doppler Ultrasonography

Abstract: <b><i>Introduction:</i></b> The basic pathophysiologic derangement of chronic kidney disease (CKD) begins with the loss of nephrons, leading to renal hemodynamic changes, eventually causing a reduced nephron count and renal hypoxia. The purpose of this study was to observe the renal oxygenation and renal hemodynamics of patients with CKD using blood oxygenation level-dependent (BOLD) magnetic resonance imaging (MRI) and intrarenal Doppler ultrasonography (IDU). <b><i>Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
6
12
0
Order By: Relevance
“… 15 , 40 A clinical study showed that after dapagliflozin treatment in DN patients, the serum TNF-α level decreased significantly, while eGFR values increased significantly when compared with the levels before treatment. 39 Our study confirmed that the decrease in the CrCl value and the increase in proteinuria during the DN stage were associated not only with high levels of TNF-α and IL-1β in the serum but also with significantly higher expression of TNF-α and IL-1β in the kidney. Additionally, the impairment of renal vascular endothelial function was confirmed by the decreased CrCl value according to some clinical research.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“… 15 , 40 A clinical study showed that after dapagliflozin treatment in DN patients, the serum TNF-α level decreased significantly, while eGFR values increased significantly when compared with the levels before treatment. 39 Our study confirmed that the decrease in the CrCl value and the increase in proteinuria during the DN stage were associated not only with high levels of TNF-α and IL-1β in the serum but also with significantly higher expression of TNF-α and IL-1β in the kidney. Additionally, the impairment of renal vascular endothelial function was confirmed by the decreased CrCl value according to some clinical research.…”
Section: Discussionsupporting
confidence: 83%
“…The eGFR value is calculated based on the SCr and UCr values of patients and their clinical age and sex. 39 In animal models, CrCl has been used extensively and is normally calculated with SCr and UCr values, urine volume and BW. 15 , 40 A clinical study showed that after dapagliflozin treatment in DN patients, the serum TNF-α level decreased significantly, while eGFR values increased significantly when compared with the levels before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we recruited HVs and patients with CKD stages 1–4 to assess inter-observer variability of the classical ROI-based method, and we found high reproducibility of both COT2* (ICC = 0.937) and MET2* (ICC = 0.910) [13]. In order to further assess the reproducibility of BOLD-MRI in patients with CKD stage 5, 10 patients with CKD stage 5 were recruited and analyzed by previous ROI-based method.…”
Section: Resultsmentioning
confidence: 99%
“…The impairment of PSV, MV, EDV, PI, and RI of the renal artery would affect renal physiology and functions. The progression of chronic kidney disease was accompanied by a decline in the renal artery blood flow velocity and an increase in renal artery resistance ( Yang et al, 2021 ). It is suggested that EDV and RI may be the best two indexes to evaluate renal function ( Abe et al, 2019 ; Di Nicolo and Granata, 2019 ).…”
Section: Discussionmentioning
confidence: 99%